Acute heart and brain failure: a case report. Issue 6 (29th November 2020) - Stuetz, Magdalena; Templin, Christian; Templin-Ghadri, Jelena-Rima; Ruschitzka, Frank; Pohl, Heiko; Hofer, Daniel
Abstract: Background: Takotsubo syndrome (TTS) is characterized by often reversible but acute heart failure occurring after an emotional or physical trigger event. The 'brain failure' counterpart is posterior reversible encephalopathy syndrome (PRES) characterized by often reversible but acute neurological symptoms. This case report elaborates on a complex clinical scenario with co-existence of coronary artery disease, TTS and PRES and discusses the pathophysiology, differential diagnosis, and management. Case summary: An 82-year-old woman presented with acute heart failure and generalized tonic-clonic seizures following an acute exacerbation of her chronic back pain. Brain magnetic resonance imaging demonstrated vasogenic oedema consistent with the diagnosis of PRES. Focal wall motion abnormalities on echocardiography without causal coronary stenoses on angiography were consistent with the diagnosis of TTS. After an interdisciplinary approach to differential diagnosis and treatment, the patient was discharged to geriatric rehabilitation without heart failure or neurological defects 4 weeks later. Discussion: TTS and PRES share significant similarities in proposed pathogenesis, epidemiology, management, and clinical outcome. This case report highlights the need for early recognition of this rare association and multidisciplinary approach to diagnosis and treatment as both heart and brain disease may require early intervention up to rapid intensive care support.